Audits as a Vaccine or Just Aspirin? - Timotej Jagrič; Tomaž Lešnik (Naše gospodarstvo/Our economy, 2017)
This paper examines the impact of audits on voluntary tax compliance in the area of value added tax in Slovenia. The analyses argues that audited taxpayers with additional tax assessments as the result of an audit display a higher level of tax compliance within the year of the audit as within the year before audit, while audited taxpayers with no irregularities on the basis of an audit do not change their behavior significantly within the same period. However, regarding the long- term effect, the results reveal the possibility of worsening tax compliance with respect to audits where an additional tax assessment was imposed and where no irregularities were discovered during an audit.